(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
The article deals with issues related to the concept of "family", the varieties of which were described in the novel "War and Peace". The author gives examples of the opposition of the Bolkonsky and Kuragin families, analyzes the method of antithesis used in the novel by the great writer